2007
DOI: 10.1136/bmj.39244.692442.55
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment for pyelonephritis in children: multicentre randomised controlled non-inferiority trial

Abstract: Objective To compare the efficacy of oral antibiotic treatment alone with treatment started parenterally and completed orally in children with a first episode of acute pyelonephritis. Design Multicentre, randomised controlled, open labelled, parallel group, non-inferiority trial. Setting 28 paediatric units in north east Italy. Participants 502 children aged 1 month to <7 years with clinical pyelonephritis. Intervention Oral co-amoxiclav (50 mg/kg/day in three doses for 10 days) or parenteral ceftriaxone (50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 18 publications
8
115
0
7
Order By: Relevance
“…The proportions of renal scarring in patients (oral group: 26%; intravenous/oral group: 46%) were comparable with previous scintigraphy investigations that documented renal scarring in 29-60% of children after acute pyelonephritis [5,15,16,21,24,30,31,35]. These results indicate that mere oral ceftibuten therapy is as efficacious as parenteral therapy, i.e.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The proportions of renal scarring in patients (oral group: 26%; intravenous/oral group: 46%) were comparable with previous scintigraphy investigations that documented renal scarring in 29-60% of children after acute pyelonephritis [5,15,16,21,24,30,31,35]. These results indicate that mere oral ceftibuten therapy is as efficacious as parenteral therapy, i.e.…”
Section: Discussionsupporting
confidence: 79%
“…a 10-fold higher range, indicating more pronounced inflammation, which, in turn, may explain the higher rate of renal scarring. Also, Montini et al [21] reported an initial CRP concentration nine-fold above the upper normal value, with a similar range of scarring in children. Nevertheless, by bag urine collection, they may have included children with false-positive urine cultures, as urine collected by catheter was not a prerequisite for inclusion as in our study and the study by Hoberman et al [14].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations